UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 18 LUBUKLINGGAU DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK - Hanisah Hanisah (Jurnal Perspektif Pendidikan, 2021)
This study aims to improve the mathematics learning outcomes of second grade students of SD Negeri 18 Lubuklinggau by using the Talking Stick learning model. This research is a classroom action research (Action Research) using the Talking Stick learning model. Based on the results of research using the Talking Stick learning model in class II SD Negeri 18 Lubuklinggau can increase, the average student learning outcome in the first cycle is 59.85 with a mastery percentage of 64.74%, in the second cycle the average learning outcome students by 69.11 with a percentage of completeness of 70.084%, and in the third cycle the average student learning outcomes of 82.66 with a percentage of completeness of 80.56%. This means that the number of students who achieve the KKM score (70) has exceeded the success criteria set, namely 75%, so it can be concluded that the Talking Stick learning model can improve students' mathematics learning outcomes.